MENUJU TAFSIR AGAMA YANG BERKEADILAN GENDER: KENISCAYAAN PERAN PEREMPUAN DALAM DUNIA PUBLIK - Sofyan Kau (Jurnal Universitas Paramadina, 2013)
AbstractThis article elaborates the inevitability of women's role in the public sphere. Islam basically does not distinguish between women and men. Both are considered equal actively involved in the public sphere, including in leadership. Necessity and equality is supported by normative texts and progressive interpretation. Discussion about the prohibition of women involvement in the public sphere and be a leader; therefore, is not Islamic thought but it is a matter of texts interpretation. Religion is believed to be universal. Justice and equality are universal thoughts of religion. Meanwhile religious interpretation remains particular interpretation and conditional. Patriarchal culture conditions also affect the interpretation of religion. Therefore, it is necessary the call for re-interpretation of gender-biased religious interpretations by a contextual reading of the religious texts and contextualise the religious interpretations.Keywords: gender equality, religious interpretation, women role, public space, contextual interpretation, and contextualization.